Pengaruh Model Pembelajaran Talking Stick Terhadap Hasil Belajar Siswa pada Tema 8 Subtema 2 di Kelas V SDN 101776 Sampali - Ronauli Gurning; Nurmayani Nurmayani; Irsan Irsan; Sorta Simanjuntak; Laurensia M. Perangin Angin (FKIP, Universitas Palangka Raya, 2024)
The research objective was to find out whether there was a positive influence from the Talking Stick learning model on student learning outcomes in theme 8 sub-theme 2 in class V SD Negeri 101776 Sampali. This research is a quantitative research, with the type of quasi-experimental research. The research sample was VA class as the experimental class and VB class as the control class, which consisted of 74 students. The research data collection instrument or technique, namely the learning outcomes test, has 20 valid questions and 10 invalid questions. Reliability of 0.88 is declared reliable with very high reliability category. The data analysis technique used is the normality test, homogeneity test, and hypothesis testing using the t-test formula. The results showed that student learning outcomes increased with the Talking Stick learning model, namely the pretest of 53.94 and the posttest of 81.97. Based on the prerequisites that were tested first, namely normal and homogeneous data. From the normality test results obtained Ltable>Lcount, namely 0.144>0.142 in the experimental class, and the control class results Ltable>Lcount, namely 0.148>0.136. So it can be concluded that the data is normally distributed. From the homogeneity test data, all data has homogeneous data according to the calculations that have been done, Ftable> Fcount, namely 1.739> 1.036 in the pretest in the experimental class and control class. In the posttest experimental class and control class Ftable> Fcount, namely 1.747> 1.070. The results of testing the hypothesis at the real level α = 0.05 obtained that tcount>ttable, namely 1.706 > 1.666. There is a positive and significant influence from the use of the talking stick learning model on student learning outcomes in theme 8 sub-theme 2 in class V SD Negeri 101776 Sampali.